STUDI FENOMENOLOGI : RESILIENCE KELUARGA PENDERITA SKIZOFRENIA DI PUSKESMAS BANTUR - Wahyu Widiastutik; Indah Winarni; Retno Lestari (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2016)
This research discusses the resilience dinamics of schizophrenia sufferer with a relapse which aims to explore the feeling of the family about the resiliece dinamics of schizophrenia sufferer with a relapse. This research metodology uses qualitative approach which involves 6 participants. The data analysis uses interpretative phenomenological analysis. The informative method uses in-depth interview technique with their parents and other relatives. The participantss are people who take care of and understand the condition of patient.The result of the research make 9 themes namely : (1) the family of the sufferer knew schizophrenia as a thougt illness; (2) the family feel uncomfortable; (3) they believed that the supernatural power causing the illness; (4) they try hard to cure the sufferer by alternative treatment; (5)the family have crisis life; (6) they regarded all misery which was experienced as God-given; (7) the family feel the care of health and environment officers; (8) they Raise from the fall; (9) they accept all condition. Keywords : family resilience, schizophrenia, relapse